2010
DOI: 10.3354/esr00245
|View full text |Cite
|
Sign up to set email alerts
|

Size-class partitioning and herding in a foraging group of green turtles Chelonia mydas

Abstract: To collect data on green turtles Chelonia mydas near the Marquesas Keys, Florida, USA, we conducted haphazard, unmarked, nonlinear transect (HUNT) surveys from a moving vessel. During HUNTs, we recorded green turtle locations and made opportunistic captures. We found a unique foraging assemblage of subadult and adult green turtles in open-water seagrass habitat (3 to 5 m deep) at the eastern Quicksands, west of the Marquesas Keys. At an adjacent area in the Marquesas Keys (Mooney Harbor), we observed juvenile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 21 publications
5
37
0
Order By: Relevance
“…The size distributions of the three FG, however, clearly demonstrated a characteristic bimodality with a low frequency of turtles of 50-70 cm SCL, similar to reports from FG in Shoalwater Bay in eastern Australia (Limpus et al, 2005), and in eastern Taiwan (Cheng and Chen, 1997). Bresette et al (2010) also reported a bimodal size distribution of pooled green turtles from Mooney Harbor and the eastern Quicksands, west of Key West, Florida, USA, although the bimodality was not noted in their study. Interestingly, the peak sizes of the present size distributions were consistent among all three FG.…”
Section: Size Compositions In the Fg And Population Trends In The Natsupporting
confidence: 75%
See 1 more Smart Citation
“…The size distributions of the three FG, however, clearly demonstrated a characteristic bimodality with a low frequency of turtles of 50-70 cm SCL, similar to reports from FG in Shoalwater Bay in eastern Australia (Limpus et al, 2005), and in eastern Taiwan (Cheng and Chen, 1997). Bresette et al (2010) also reported a bimodal size distribution of pooled green turtles from Mooney Harbor and the eastern Quicksands, west of Key West, Florida, USA, although the bimodality was not noted in their study. Interestingly, the peak sizes of the present size distributions were consistent among all three FG.…”
Section: Size Compositions In the Fg And Population Trends In The Natsupporting
confidence: 75%
“…In several FG, green turtles were known to demonstrate size-partitioning of habitats as a result juveniles inhabiting shallower waters, and larger turtles inhabiting deeper water (Balazs, 1980;Bresette et al, 2010;Koch et al, 2007;Limpus et al, 2005;López-Mendilaharsu et al, 2005). Such size-partitioning of habitats has been explained by the minimization of predation risk.…”
Section: Possible Factors Contributing To the Bimodal Size Distributionsmentioning
confidence: 97%
“…One Bermuda green turtle was recaptured in St. Lucie County, Florida, fitted with a satellite transmitter and subsequently tracked to foraging grounds west of the Marquesas Islands (50 km W of Key West) where it remained for at least eight months (D. Bagley, personal commun.). This area west of the Marquesas has recently been shown to serve as adult foraging habitat for C. mydas (Bresette et al, 2010).…”
Section: Chelonia Mydasmentioning
confidence: 99%
“…Once we brought a turtle aboard the boat, we took standard measurements, including curved (CCL) and straight (SCL) carapace lengths from the anterior notch to the last posterior marginal scute, and took photographs to document carapace and skin ano malies. Based on external assessment of animal size and tail size, we categorized them into subadult-sized (65−90 cm SCL; Bresette et al 2010) and adult-sized (> 90 cm SCL) females or males; male turtles of which we took tail measurements (n = 5) had cloaca-tip lengths ≥ 5.5 cm. We tagged each animal with a passive integrated transponder (PIT) in the right shoulder and affixed an individually numbered flipper tag to each front flipper.…”
Section: Deployment Of Satellite and Acoustic Tagsmentioning
confidence: 99%